SCIENCE AND ENLIGHTENMENT SEMALI IN DICTIONARY UNITS - Rahmatullaeva Dilafrozkhan Shukhratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
As we know, the great linguist F.Sossyur had been thinking about linguistic relations, commenting separately on the associative relations in the language system and the syntagmatic relations in the speech process. The scientist shows paradigmatic relations under the interpretation of associative attitudes. In subsequent scientific research, the paradigmatic and associative relationships differ among themselves[1]. In the second quarter of the last century, the issue of researching language in close connection with the individual imagination, perception was put on the agenda in linguistics. As a result of this, the attention of linguists was attracted by the relationship of the owner of language and language. This, in turn, led to an increase in interest in such problems as speech and its creation, perception. At the moment, new methods of analysis of the study of the relationship between the character and its users have come to the field[2]. [1] Солнцев В.М. Язык как системно-структурное образование. Москва: Наука, 1977; Новиков Л.A. Семaнтикa русского языкa. – Москва: Высшaя школa, 1982 ва бошқалар. [2] Сафаров Ш. Прагмалингвистика. Тошкент: Ўзбекистон миллий энциклопедияси, 2008; Ҳакимов М.Х. Ўзбек тилида матннинг прагматик талқини: Филол.фанл.д-ри.... дисс.автореф. Тошкент, 2001; Худайберганова Д.С. Ўзбек тилида бадиий матнларнинг антропоцентрик талқини: : Филол.фанл.д-ри.... дисс.автореф. Тошкент, 2015; Рустамов Д. Лексемалар миллий-маданий хосланган семемасининг лингвомаданий тадқиқи: Филол. фанл. бўй. фалс .докт. дисс. автореф. – Фарғона, 2018; Рустамова Д.А. Метафорик эвфемизациянинг лингвокультурологик ва социопрагматик аспектлари: Филол. фанл. бўй. фалс .докт.дисс.автореф. – Фарғона, 2018; Насруллаева Г.С. Антропоцентрик метафоранинг лисоний, когнитив ва лингвомаданий аспекти: Филол. фанл .бўй. фалс. доктори.... дисс. автореф. Фарғона, 2019 ва бошқалар.